TERMIN „PIRAT” W PISMACH CYCERONA – INWEKTYWA CZY COŚ WIĘCEJ? - Tarwacka, Anna (Zeszyty Prawnicze, 2016)
The Term ‘Pirate’ in Cicero’s Works – Invective or More? Summary Being a remarkably acute politician, Cicero was aware of the fact that in order to discredit his opponents he had to appeal to his audience’s deepest fears. That is why he called his enemies pirates – the Romans were affraid of maritime bandits who constituted a significant threat at the Mediterranean. In his early speeches, such as Pro Roscio, Cicero used the term ‘pirate’ as an invective. In the Verrine orations piracy was one of the basic topics: Verres himself was called pirate but he was also accused of tollerating piracy and taking bribes from pirate leaders. Cicero’s most bitter enemy Clodius was called pirate in order to show that his tribunate was illegal. It was the first time when piracy was used not only as an invective but as a part of legal reasoning. It was based on Cicero’s theory that pirates were common enemies of all mankind fully expressed in the treaty De officiis. Campaingning for the last time in his life against Antonius Cicero called him an archpirate thus giving Octavian a possibility to impunely break all the agreements with him, because only oaths given to war enemies were binding whereas those given to pirates were not sanctioned by the law of war.